PEMBUATAN BINDERLESS PAPAN PARTIKEL DARI BUNGKIL JARAK KEPYAR (Ricinus communis L.) - Ika Amalia Kartika, Iddea Qodriaza Kautsar, Farah Fahma (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2015)
ABSTRACT Castor cake meal is by-product generated from castor oil industry which contains high protein (38.58%). This research used castor cake meal as raw material for binderless particleboard production. The objective of this research was to determine the effect of pressing temperature and pressure on physical and mechanical properties of particleboard, and to obtain the optimum pressing temperature and pressure for particleboard production. The experimental design used Central Composite Design with variables of temperature (160-180°C) and pressure (160-200 kgf/cm2). Data obtained were analyzed by ANOVA (α = 0.05) and Response Surface Method. The physical and mechanical properties of particleboard were tested based on JIS A 5908:2003. Generally the physical and mechanical properties of particleboard were not accordance to JIS A 5908:2003 except for moisture content. Pressing temperature and pressure affected the physical and mechanical properties of particleboard. The optimum temperature and pressure to produce the particleboard from castor cake meal were respectively 160°C and 200 kgf/cm2 with density of 0.94 g/cm3, moisture content of 5.85%, water absorption for 2 h of 42.9%, water absorption for 24 h of 80.4%, thickness swelling for 2 h of 27.8%, thickness swelling for 24 h of 36.2%, MOE of 2726.9 kgf/cm2 and MOR of 14.9 kgf/cm2. Keywords: Binderless particleboard, castor cake meal MOE, MOR